Factors influencing continuance intention to use social media among malaysian manufacturing smes: the mediating effect of social media usage - Lim, Ming Fook (2022)
Malaysian SMEs were discovered to be using social media in their businesses. This is because social media is now one of the most important marketing channels for businesses. The role of social media, on the other hand, has been inconsistent and has yet to be heavily focused on the SME Manufacturing field. Consequently, the continuance intention of the use of social media remains unknown to date. Therefore, the purpose of this study is to examine the factors influencing continuance intention to use social media among Malaysian manufacturing SMEs. In addition, the study also examines the mediating effect of social media usage on the relationship of technological, organizational, environmental context, and inter-organizational relationship (independent variables) and continuance usage intention (dependent variable). In terms of operation, this study adapted the Technological-Organizational-Environmental framework (TOE) and Diffusion of Innovation Model (DOI) to predict and understand the factors influencing continuance intention to use social media among Malaysian manufacturing SMEs. A set of data from 185 respondents from manufacturing SME’s owner, marketing manager, or marketing executive were used by analyzed with SPSS version 26 and SmartPLS 3.3.3. Bootstrapping results showed relative advantage, partner’s pressure, communication, and networking have significant relationships with social media usage. Furthermore, social media usage has a significant relationship with continuance intention. The mediation analysis results indicated that social media usage mediated the relationships between relative advantage and communication. Owners or marketing departments at manufacturing SMEs may find the study's findings useful as guidelines for adopting efficient B2B social media marketing strategies, apart from extending the body of knowledge in social media usage and continuance usage intention. Limitation of the study and future research recommendations have also been done.